Data from: Phylogenomic species delimitation dramatically reduces species diversity in an Antarctic adaptive radiation ... - Parker, Elyse; Dornburg, Alex; Struthers, Carl; Jones, Christopher; Near, Thomas (Dryad, 2021)
Application of genetic data to species delimitation often builds confidence in delimitations previously hypothesized using morphological, ecological, and geographic data and frequently yields recognition of previously-undescribed cryptic diversity. However, a recent critique of genomic data-based species delimitation approaches is that they have the potential to conflate population structure with species diversity, resulting in taxonomic oversplitting. The need for an integrative approach to species delimitation, in which molecular, morphological, ecological, and geographic lines of evidence are evaluated together, is becoming increasingly apparent. Here, we integrate phylogenetic, population genetic, and coalescent analyses of genome-wide sequence data with investigation of variation in multiple morphological traits to delimit species within the Antarctic barbeled plunderfishes (Artedidraconidae: Pogonophryne). Pogonophryne currently comprises 29 valid species, most of which are distinguished solely by ... : Parker_et_al2021_supplement.docx Supplementary Tables S1-11 and Supplementary Figures S1-S8. min58.phy Dataset of concatenated sequences including all loci shared across 25% (58 of 228) individuals min116.phy Dataset of concatenated sequences including all loci shared across 50% (116 of 228) individuals min174.phy Dataset of concatenated sequences including all loci shared across 75% (174 of 228) individuals noOut_min55.ustr Dataset excluding all outgroup taxa and including randomly-sampled unlinked SNPs from loci shared across 25% (55 of 218) individuals analyzed using DAPC noOut_min110.ustr Dataset excluding all outgroup taxa and including randomly-sampled unlinked SNPs from loci shared across 50% (110 of 218) individuals analyzed using DAPC noOut_min165.ustr Dataset excluding all outgroup taxa and including randomly-sampled unlinked SNPs from loci shared across 75% (165 of 218) individuals analyzed using DAPC noOut_min197.ustr Dataset excluding all outgroup taxa and including randomly-sampled unlinked ...